Ridge-based fingerprint matching using hough transform - Marana, Aparecido Nilceu [UNESP]; Jain, Anil K. (Institute of Electrical and Electronics Engineers (IEEE), Computer Soc, 2005)
Despite the efficacy of minutia-based fingerprint matching techniques for good-quality images captured by optical sensors, minutia-based techniques do not often perform so well on poor-quality images or fingerprint images captured by small solid-state sensors. Solid-state fingerprint sensors are being increasingly deployed in a wide range of applications for user authentication purposes. Therefore, it is necessary to develop new fingerprint-matching techniques that utilize other features to deal with fingerprint images captured by solid-state sensors. This paper presents a new fingerprint matching technique based on fingerprint ridge features. This technique was assessed on the MSU-VERIDICOM database, which consists of fingerprint impressions obtained from 160 users (4 impressions per finger) using a solid-state sensor. The combination of ridge-based matching scores computed by the proposed ridge-based technique with minutia-based matching scores leads to a reduction of the false non-match rate by approximately 1.7% at a false match rate of 0.1%. © 2005 IEEE.
Keywords: Computational methods; Database systems; Hough transforms; Image processing; Image quality; Optical sensors; Fingerprint images; Fingerprint matching; Solid-state sensors; User authentication; Pattern matching